A beginning to digital appraisals of student’s essays - experiential learning in bs8101 : evaluating progress journals and grading rubric - Yao, Leon Jinchi (2019)
The primary objective of this study is to evaluate the effectiveness of a DEEP GER course, BS8101 offered in NTU. BS8101 takes the approach of Kolb’s experiential learning by challenging students to develop a recipe and document their learnings and conclusions in a progress journal. This progress journal makes up a quarter of the student’s final grade in this course and due to the nature of documenting experiences, components of the journal is difficult to quantify and thus grade. Including the skillset required to conduct experiential learning, the class size of BS8101 is limited by the ability and resource of the course coordinator. By evaluating the progress journals and the rubric used to mark the journals, results show that it is difficult to introduce new professors into the course, but AI can be introduced to grade components of the progress journal. Results also suggests that students may be unsure of how to document their learning experiences by the way most of them change the way they format their journals when given guidance, attention should be given to guiding students to go through Reflective Observation. BS8101 is a alternative learning approach that may only accommodate a small amount of students, but with more work and the assistance of AI, more students may be able to experience experiential learning in BS8101.